Triade aristotélicienne, matières bodéliennes, genres médiévaux : dépasser les apories génériques avec Gérard Genette - Géraldine Toniutti (Perspectives Médiévales)
The article have the intention of verifying the pertinence of Gérard Genette’s theory of the literary genre, applied to the medieval literature. By rereading Aristotle’s Poetics, Genette proposes a way of using this concept, that prevents from essentializing the generic categories. His theory, which should be universal, should overcome the reticences of the medievists towards the application of the concept of genre to medieval literature. The system that Genette offers also invites to question the status of “matière”, offen considered as a synonymous of “genre”. When we overcome this theoretical problems, we can maintain the legitimacy of the concept of genre and its application to the medieval literature; the literary field is always organized on relations, and the medieval literature conforms to this rule.